W-Doping of Dense NMC811 Hydroxide through Wet-Impregnation and Its Impact on Crystal Structure, Phase Transition Related Gas Evolution and Electrochemical Performance at Elevated Upper Cut-Off Voltage. Issue 12 (1st December 2022) - Dalkilic, Mert; Schmidt, Alexander; Schladt, Thomas D.; Axmann, Peter; Wohlfahrt-Mehrens, Margret; Lindén, Mika
Abstract : Doping of Ni-rich LNMC cathode materials with tungsten via solid-state route has been shown to stabilize the materials against structural degradation at high voltages during electrochemical cycling. Here we use a wet-chemical doping method to homogeneously introduce 0.5 mol% tungsten into dense NMC811 (Li[(Ni0.8 Mn0.1 Co0.1 )]O2 ), followed by a detailed structural and electrochemical characterization. A homogeneous distribution of W in the materials was evidenced by elemental mapping and TOF-SIMS. The increase in bond-dissociation energy to oxygen (BDEO) of the transition metal (TM) site led to compressed slab thickness (TMO6 octahedron width in c -direction), indicating shorter, and thus strengthened, TM–O bonds, as also confirmed by TGA-MS results. Importantly, statistical analysis of electron backscatter diffraction (EBSD) data revealed a W-induced radial alignment of a – b planes of the primary particles. The cycling stability of the doped material was more than 7% higher for the W-doped (92.4%) as compared to the undoped NMC811 (85.3%) material at a higher upper cut-off voltage of 4.5 V vs Li/Li + . Furthermore, the voltage decay was lower (0.2 V vs 0.29 V), leading to >2% lower energy loss (5.3% vs 7.4%) for the W-doped material.